Local T cell subsets in mumps meningitis. Issue 11 (November 1983) - Nagai, H; Morishima, T; Morishima, Y; Isomura, S; Suzuki, S
Abstract : In the acute phase of mumps meningitis, more than 85% of the cells in cerebrospinal fluid (CSF) were OKT 3 positive, while 76% of the peripheral mononuclear cells (PMN) were OKT 3 positive. The ratio of OKT 4:8 positive cells in CSF was significantly lower than that in PMN, showing that suppressor/cytotoxic T cells had selectively accumulated in CSF. In addition, 58% of CSF cells were immune associated (Ia) positive, probably activated T cells.